2021
DOI: 10.1371/journal.pgen.1009386
|View full text |Cite
|
Sign up to set email alerts
|

Genomic rearrangements generate hypervariable mini-chromosomes in host-specific isolates of the blast fungus

Abstract: Supernumerary mini-chromosomes–a unique type of genomic structural variation–have been implicated in the emergence of virulence traits in plant pathogenic fungi. However, the mechanisms that facilitate the emergence and maintenance of mini-chromosomes across fungi remain poorly understood. In the blast fungus Magnaporthe oryzae (Syn. Pyricularia oryzae), mini-chromosomes have been first described in the early 1990s but, until very recently, have been overlooked in genomic studies. Here we investigated structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 89 publications
(153 reference statements)
2
71
1
Order By: Relevance
“…Model M3 and M8 passed the chi-square test at a significance level of 1% ( S2 Table ). Ancestral state reconstruction was performed by a codon based maximum likelihood analysis with codeml (included in the PAML v4.9 package) according to [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Model M3 and M8 passed the chi-square test at a significance level of 1% ( S2 Table ). Ancestral state reconstruction was performed by a codon based maximum likelihood analysis with codeml (included in the PAML v4.9 package) according to [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…These SVs may lead to the formation of accessory* regions, or even chromosomes. A study of SVs in four strains of the blast fungus Magnaporthe oryzae showed that accessory chromosomes probably emerged from interchromosomal translocations between core* and accessory* chromosomes and segmental duplications* of core* chromosomes (Langner et al ., 2021). These accessory* regions or chromosomes often are enriched in TEs, rapidly evolving genes, such as effector* genes, and various types of SVs relative to other regions of the genome.…”
Section: The Shaping Of Fungal Plant Pathogen Genomes By Structural V...mentioning
confidence: 99%
“…More complex events, known as chromoanagenesis, combine a cascade of chromosomal rearrangements 1 . Over the past few years, structural variants and complex genomic rearrangements have been implicated in various phenotypes: cancer 2 , 3 , rare disorders 4 9 and common diseases 10 in humans, reproduction traits in pigs 11 , virulence traits in plant pathogenic fungi 12 , local adaptation in maize 13 , and behavior in Caenorhabditis elegans ( C. elegans ) 14 . However, the technologies and methods used to identify SVs and complex rearrangements are still multifaceted and no approach has yet been recognized as standard.…”
Section: Introductionmentioning
confidence: 99%